Peningkatan Daya Saing Produk Batik Alam Jepara Melalui Penciptaan Cap Alternatif Dan Penggunaan Bahan Pewarna Alam Yang Ramah Lingkungan - Widagdo, Jati; Zeyn, Akhmad Khanif; Komaryatin, Nurul; Roosdhany, Rifqy (Jurnal Pengabdian kepada Masyarakat UBJ, 2024)
Current economic developments require high creative power to deal with highly disruptive markets with rapid changes. This is in line with the creative economy policy launched by the government. Batik is one of the products of the creative economy that was developed by Indonesia long ago. In Jepara, currently there are 32 Batik SMEs, one of which is Batik Kembang Mulyo, which is different from the others because it produces natural batik using environmentally friendly materials, namely utilizing biological natural resources through natural coloring. Of course, this needs to be balanced with the existence of innovative batik motifs so that they are not monotonous, where previously only limited to plant motifs, now it is necessary to create new designs through postmodern batik designs or artistic designs so that they are more marketable and competitive in the market. Through this community service activity by collaborating with MSME partners, it is hoped that the Kembang Mulyo batik industry will be able to develop the batik industry in Jepara so that it can compete in the market. The dedication method is carried out through Jepara Nature Batik Fashion Show activities, seminars in the form of lectures, focus group discussions (FGD), and workshops.